Analysis of transcriptional profiles of Saccharomyces cerevisiae exposed to bisphenol A - MERTOĞLU, BÜLENT; BEREKETOĞLU, CEYHUN; ARĞA, KAZIM YALÇIN (SPRINGER, 2017)
Bisphenol A (BPA), an endocrine disrupting chemical, is used as a monomer in the production of epoxy resins and polycarbonates, and as a plasticizer in polyvinyl chloride. As such, it is produced in large quantities worldwide and continuously leaches into the environment. To capture the genome reprogramming in eukaryotic cells under BPA exposure, here, we used Saccharomyces cerevisiae as model organism and analyzed the genome-wide transcriptional profiles of S. cerevisiae BY4742 in response to BPA, focusing on two exposure scenarios: (1) exposure to a low inhibition concentration (50 mg/L; resulting in < 10 % inhibition in cell number) and (2) a high inhibition concentration (300 mg/L; resulting in > 70 % inhibition in cell number). Based on the transcriptional profiling analyses, 81 genes were repressed and 104 genes were induced in response to 50 mg/L BPA. Meanwhile, 378 genes were downregulated and 606 genes were significantly upregulated upon exposure to 300 mg/L BPA. While similar processes were affected by exposure to distinct BPA concentrations, including mitochondrial processes, nucleobase-containing small molecule metabolic processes, transcription from the RNA polymerase II promoter, and mitosis and associated processes, the number and magnitude of differentially expressed genes differ between low and high inhibition concentration treatments. For example, exposure to 300 mg/L BPA resulted in severe changes in the expression levels of several genes involved in oxidative phosphorylation, the tricarboxylic acid cycle, ribosomal activity, replication, and chemical responses. Conversely, only slight changes were observed in the expression of genes involved in these processes in cells exposed to 50 mg/L BPA. These results demonstrate that yeast cells respond to BPA in a concentration-dependent manner at the transcriptional level via different genes and provide insight into the molecular mechanisms underlying the modes of action of BPA.
Keywords: Bisphenol A; Transcriptional profiles; Saccharomyces cerevisiae; Exposure; CYTOCHROME-C-OXIDASE; CELL-WALL INTEGRITY; RESPIRATORY-CHAIN; GENE-EXPRESSION; BINDING-PROTEIN; BC(1) COMPLEX; SUCCINATE-DEHYDROGENASE; S-ADENOSYLMETHIONINE; DNA MICROARRAY; DUAL FUNCTION